Impact of Green Marketing Mediating Brand Love on Purchasing Decisions for Batik MSME Products in Central Java - Syafi'ah; Victor Prasetya; Melan Susanty Purnamasari; Oki Anggraeni Oki; Reza Rahmadi Hasibuan Reza (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2024)
In an era where consumers are increasingly aware of the importance of sustainability, Batik SMEs in Central Java find themselves in a strategic position to leverage the trend of Green Marketing as a tool to enhance their competitiveness. The objective of this research is to analyze the impact of green marketing mediating the relationship between brand love and purchasing decisions in Batik Micro, Small, and Medium Enterprises (UMKM) in Central Java. The total population of manufacturing company employees in Central Java in 2022 is approximately 465.654. Using the Slovin's formula, a sample of 219 Actor and MSME Batik Consumers was obtained with a confidence level of 5%. A purposive random sampling technique was applied to select a sample of Actor and Batik MSME Consumers, thereby ensuring good representation of the various Batik MSMEs in Central Java. To analyze the data and test the research hypothesis, the Mediation Regression method was used with the help of SPSS software. The results of this research are that brand love has a significant and positive influence on purchasing decisions, then green marketing mediates the relationship between brand love and purchasing decisions among Batik MSMEs in Central Java.